SPIRITUAL ENTREPRENEURSHIP DI PESANTREN ENTREPRENEUR AL-MAWADDAH KUDUS - M. Sofyan Alnashr; Muhammad Labib (Islamic Review: Jurnal Riset dan Kajian Keislaman, 2019)
This study aims to map spiritual values ​​that encourage Pesantren Entrepreneur Al-Mawaddah to conduct entrepreneurship movements and their application in real action. This research is a field research with qualitative-descriptive method which took place at the Pesantren Entrepreneur Al-Mawaddah, Honggosoco Village, Jekulo, Kudus. As a method of searching data, interview, observation and documentation techniques have been carried out. Then, in the analysis phase has been used Miles and Huberman analysis techniques with 4 stages of analysis ; collecting data, data reduction, data display, verification and drawing conclusions. The results of this study have mapped Core Values ​​Ahli Sorga (which contains 9 values) as a spiritual value that encourages Pesantren Al-Mawaddah to develop entrepreneurship. This value is the result of reflection and internalization of the gusjigang ideology inherited from Sunan Kudus. These spiritual values ​​have been implemented by pesantren in the form of: (1) pesantren which are honest and trustworthy in carrying out various business fields and safeguarding the products of the community, (2) charity activities in the form of mass circumcision and orphanage, sewing skills training and make snacks, agricultural technology training, (3) balance in carrying out ibadatullah (compulsory worship, recitation of kitab kuning) and imarathul ardh in the form of entrepreneurship development, (4) formulation of vision and action conducted by founders and caregivers from a young age, encouraging santri to have similar visions and missions. (5) making Core Values Ahli Sorga ​​as an autosuggestion in santri to have the spirit of entrepreneurship.